Analisis pengaruh Produk Domestik Regional Bruto (PDRB) dan Jumlah Penduduk terhadap Belanja Pelayanan Publik Indonesia - Syaputri, Ayu Geby Gisela; Ulum, Muhammad Bahrul (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The Purpose of this study was to determine the Effect of Economic Growth with indicator Gross Domestic Regional Product (GDRP) and total population on the Public Service Spending in Indonesia start from 2014 – 2023, this study uses panel data regression or Ordinary Least Square. In this study was concluded that Gross Domestic Product have a positive and not significant on the Public Service Spending whereas Total Population have a positive and significant on the Public Service Spending, the effect significant or not significant all variables can be affected by annual data on the listed.As the Total Population was increases, it is necessary have a role play legislation on the Public Service Spending so that created good Public Service Spending for public.